A shorter course of DAPT after stenting. Issue 2 (February 2018) - Lanham, Jason; Rogers, Tyler
Abstract : N/A: Gargiulo G, Windecker S, da Costa BR, Feres F, Hong MK, Gilard M, et al. Short term versus long term dual antiplatelet therapy after implantation of drug eluting stent in patients with or without diabetes: systematic review and meta‐analysis of individual participant data from randomised trials. BMJ . 2016; 355:i5483.